KESULITAN SISWA MENYELESAIKAN SOAL MENGENAI JARAK DALAM BANGUN RUANG BERDASARKAN MODEL KESULITAN NEWMAN - Syafiudin, Muhamad Arif; Hartoyo, Agung; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know and describe students difficulties in solving problems about distance in solid geometry based on the Newman’serror model in high school". This research is qualitative researchusing descriptive method with survey research form. The subjects of this research were 34 students of class XII MIA 3 inSMA N 9 Pontianak. The object of this research is the difficulties of students in solving problems about distance in solid geometry based on the Newman’serror model. Data collection techniques used are measurement techniques.Data collection tool used test and interview. The research results showed that the difficulties experienced by students of class XII MIA 3 SMA N 9 Pontianakwere: (1) students misunderstood the problem, (2) students could not write important information (what was known and what was asked of question) completely, (3) students are not able to change the problem to mathematical form, (4) students cannot choose the right operations and procedures, (5) students do not smoothly use operations and procedures, and (6) students cannot represent the results of the mathematical process into contextual form. Keywords: Students Difficulties, Distance in Solid Geometry, Newman's Error Model